MUSLIM FRIENDLY TOURISM AND WESTERN CREATIVE TOURISM: THE CONCEPTUAL INTERSECTION ANALYSIS - Hasanah, Syarifah (UNISSULA, 2020)
With the present boom and widespread Muslim friendly destinations, extensive research has been carried out on this concept. However, these works have not adequately addressed the issue of creativity, which is widely discussed in the current study of Western tourism literature or so-called creative tourism. This paper discusses the creativity concept embedded in the theoretical and empirical research on Muslim friendly tourism. Specifically, this paper addresses the issue of creativity in Muslim friendly tourism. To achieve this, systematic literature review and the content or document analysis were employed for data collection and the analysis. This research argued that the current components of Muslim friendly destination are yet inadequate, notably the creativity element. In conclusion, by closely examining creativity in the Muslim friendly tourism concept, this paper sheds new light on the rarely acknowledged issue of creative tourism from an Islamic perspective.